Role of guanylate-binding protein 1 in the proliferation of invasive lung adenocarcinoma cells - Kumada, Takashi; Mimae, Takahiro; Tsubokawa, Norifumi; Kushitani, Kei; Takeshima, Yukio; Miyata, Yoshihiro; Okada, Morihito (Frontiers in Oncology, 2025)
BackgroundGuanylate-binding protein 1 (GBP1) is involved in the malignant progression of lung adenocarcinoma, particularly in the acquisition of invasive potential. However, its role in tumor proliferation and therapeutic viability in invasive lung adenocarcinomas remains unclear.MethodsThis study included 99 patients with invasive lung adenocarcinoma, excluding those with non-invasive lepidic components, who had undergone complete pulmonary resection. Immunohistochemical staining was performed to examine the presence of GBP1, and its prognostic significance was assessed using uni- and multi-variable Cox regression analyses. Additionally, the expression levels of GBP1 gene and protein levels were evaluated in lung adenocarcinoma cell lines (PC-9, A549, NCI-H322, NCI-H441, NCI-H820, and ABC-1), and its proliferative role in these cell lines was analyzed using specific inhibitors targeting GBP1.ResultsGBP1 expression was detected in 45 (45.5%) patients. The 5-year overall survival rates for GBP1-positive and -negative patients were 66.0% (95% confidence interval (CI): 46.3–80.0%) and 85.7% (95% CI: 72.0–93.0%), respectively (P = 0.029). The multivariable analysis demonstrated that GBP1 positivity was an independent factor for poor overall survival (hazard ratio [HR] = 2.52 [95% CI: 1.02–6.22], P = 0.045). GBP1 gene and protein were markedly expressed in NCI-H820 than in NCI-H322 and ABC-1. The inhibitor targeting GBP1 significantly suppressed the growth of NCI-H820 but not that of NCI-H322 or ABC-1.ConclusionsGBP1 is a prognostic factor that may be involved in the proliferation of invasive lung adenocarcinoma, suggesting that inhibiting GBP1 activity may be a promising therapeutic approach for lung adenocarcinoma patients expressing GBP1.